Green Three-component Synthesis of Merocyanin Dyes Based on 4-Arylideneisoxazol-5(4H)-ones - Damghani, Fatemeh K.; Kiyani, Hamzeh; Pourmousavi, Seied A. (Current Green Chemistry, 2020)
A one-pot three-component reaction promoted by choline chloride: zinc(II) chloride deepeutectic solvent (ChCl-ZnCl2 DES) in an aqueous medium for the synthesis of several merocyanin dyes based on isoxazol-5(4H)-ones is presented. This three-component approach is efficient, clean, experimentally simple, convenient, safe, and environmentally friendly. This reaction was performed at room temperature without using energy sources such as heat, microwave and ultrasound waves. Nonuse of toxic solvents, available materials, one-vessel, no wasted reagents, simple preparation, and recyclability of DES are other important points of this method that is significant from the perspective of green chemistry.
Keywords: isoxazol-5(4H)-ones